1955
DOI: 10.1172/jci103082
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Alpha-Ketolic Steroid Metabolites of Cortical Hormones Administered to Subjects With Adrenal Cortical Insufficiency 1

Abstract: The analysis of urinary excretory products following the administration of known compounds is one of the classical methods for the study of their metabolism. The developments in paper chromatographic (1) and micro-analytic (2) technics and the use of glucuronidase hydrolysis (3) have considerably decreased the difficulties of investigating steroid metabolism by this method. Using these newer technics, we have studied the urinary excretion pattern of the major alpha-ketolic steroids after the administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
1

Year Published

1955
1955
1966
1966

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…after ACTH. It is evident from this and previous studies (1) as well as the position and relatively small absorption at 245 m,u (not shown) in these regions that the twin alphaketolic peaks in the first portion of fraction X in the other subjects are probably formed by H4F and H4E. The increased excretion of hydrocortisone (F) after administration of ACTH is also indicated.…”
supporting
confidence: 62%
See 4 more Smart Citations
“…after ACTH. It is evident from this and previous studies (1) as well as the position and relatively small absorption at 245 m,u (not shown) in these regions that the twin alphaketolic peaks in the first portion of fraction X in the other subjects are probably formed by H4F and H4E. The increased excretion of hydrocortisone (F) after administration of ACTH is also indicated.…”
supporting
confidence: 62%
“…Methods employed and their limitations have been presented previously (1). Terminology has been previously discussed (1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations